2008
DOI: 10.1111/j.1745-7254.2008.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of antimony compounds in oncology

Abstract: Antimony, a natural element that has been used as a drug for over more than 100 years, has remarkable therapeutic efficacy in patients with acute promyelocytic leukemia. This review focuses on recent advances in developing antimony anticancer agents with an emphasis on antimony coordination complexes, Sb (III) and Sb (V). These complexes, which include many organometallic complexes, may provide a broader spectrum of antitumoral activity. They were compared with classical platinum anticancer drugs. The review c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…47 In addition, some Sb compounds show antitumor activity. 48 On the other hand, hematuria, dermatitis, nausea, vomiting, diarrhea, pharyngitis, and nephrotoxicity were reported to be clinical symptoms of Sb toxicosis. 49 It was also reported that Sb workers had an increased incidence of lung cancer.…”
Section: ·1 Antimony In Biology Toxicology and Medicinementioning
confidence: 99%
“…47 In addition, some Sb compounds show antitumor activity. 48 On the other hand, hematuria, dermatitis, nausea, vomiting, diarrhea, pharyngitis, and nephrotoxicity were reported to be clinical symptoms of Sb toxicosis. 49 It was also reported that Sb workers had an increased incidence of lung cancer.…”
Section: ·1 Antimony In Biology Toxicology and Medicinementioning
confidence: 99%
“…Meglumine antimonate and sodium sti- (Santos et al, 2008). In addition, an Sb compound was developed as an antitumor agent (Sharma et al, 2008). A Ge-containing drug, propagermanium, was evaluated for potential use as an immunomodulator (Hirayama et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the antimony compounds used for the treatment of leishmaniasis have also been investigated for potential antitumour activity [56][57][58][59]. Sodium stibogluconate has been evaluated for antileukaemic activity against the myeloid leukaemia cell lines (NB4, HL-60 and U937) and shown to induce differentiation of acute myeloid leukaemia.…”
Section: Antimony Compoundsmentioning
confidence: 99%
“…Further, the results suggest that sodium stibogluconate is functioning as a PTPase inhibitor in the leukaemia cells [57]. It appears that most attention in developing new antimony based anticancer agents has been directed to newly synthesized molecules [58,59]. The following is an overview of recent studies in this area.…”
Section: Antimony Compoundsmentioning
confidence: 99%